INTERCULTURAL COMMUNICATION IN THE PROCESS OF EUROPEAN INTEGRATION - AKSYONOVA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article is dedicated to the issues of intercultural communication and its challenges in the context of European integration. The study aims to analyze and generalize the existing theoretical foundations of intercultural communications and identify the main barriers that arise in the process of intercultural communication in the context of European integration.The study presents theoretical approaches to analyzing intercultural interaction, its significance for adapting to cultural diversity, and its role in shaping a common European identity. The concept of "intercultural communication" is analyzed, with special attention given to the concepts of leading scholars, which allow evaluating the impact of cultural differences on communication effectiveness, which is crucial in light of the study's objective.It is justified that intercultural communication is not only a verbal exchange, but a complex system of non-verbal signals, cultural codes, and contextual factors. It has been revealed that intercultural communication promotes mutual understanding and serves as a key instrument in the processes of globalization, international cooperation, and European integration. The study highlights the importance of systemic, cognitive, and network approaches to analyzing intercultural communication. It is determined that the systemic approach is used in studies within the concept of an information society, where special attention is paid to the means of transmitting, storing, and interpreting information between cultures; the cognitive approach focuses on the processes of perception, processing, and interpretation of information during intercultural communication; and the network approach is based on evaluating the role of global media, social networks, and platforms in shaping the image of national cultures.The article analyzes the problems arising in the process of European integration due to cultural differences, particularly linguistic barriers, sociocultural stereotypes, and historical contradictions. The research found that intense migration processes, on the one hand, enrich the cultural environment of the EU, but on the other hand, create certain social difficulties that require a systematic approach to migrant integration. It is determined that to overcome these justified barriers, it is advisable to implement educational programs, cultural exchange platforms, language policies, digital technologies, and programs for migrant support.Overall, the study shows that intercultural communication is an essential component of the European integration processes, contributing to the development of mutual understanding, tolerance, and cooperation among EU countries, and emphasizes the need for the implementation of appropriate strategies for effective intercultural interaction.
Keywords: communication; culture; intercultural communication; European integration; globalization; digitalization; intercultural dialogue; migration